The Effects of Spirituality on Depression, Anxiety, and Post-Traumatic Stress Disorder: A Systematic Review - Okan, Nesrullah; Sahin, Yahya (Springer, 2026)
This study aims to systematically evaluate the findings of quantitative research examining the relationship between spirituality and depression, anxiety, and post-traumatic stress disorder (PTSD). The systematic review was conducted in accordance with the PRISMA guidelines, and the study protocol was pre-registered in the PROSPERO database. A comprehensive literature search conducted in PubMed, Web of Science Core Collection, Scopus, and PsycINFO databases resulted in a total of 17 studies meeting the predefined inclusion and exclusion criteria being included in the review. The findings were evaluated using a narrative synthesis approach. The vast majority of the studies reviewed showed that spirituality and spiritual well-being are inversely related to symptoms of depression and anxiety. In clinical and community-based samples, lower depressive and anxious symptoms were reported in individuals with higher levels of spiritual well-being. Findings in the context of post-traumatic stress disorder (PTSD) revealed that spirituality is not a unidirectional protective factor. Positive spiritual coping and spiritual functioning were associated with lower PTSD symptoms, whereas spiritual conflict and unmet spiritual needs were associated with higher levels of psychological distress. In conclusion, this systematic review demonstrates that spirituality exhibits meaningful relationships with mental health, but that its effects must be considered in a manner sensitive to contextual and individual differences.
Keywords: Spirituality; Depression; Anxiety; Post-traumatic stress disorder; Systematic review